ANALISIS PERAN KEPALA SEKOLAH DALAM MENJAMIN KUALITAS PEMBELAJARAN DI UPTD SDN 333 TANGKOLI KECAMATAN MANIANGPAJO KABUPATEN WAJO - Rohanah; Muhammad Arafah; Tenri Sau (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of the school principal in ensuring the quality of learning at UPTD SDN 333 Tangkoli, Maniangpajo Subdistrict, Wajo Regency. The focus of the study is on the principal’s three main roles: as a learning leader, manager, and supervisor. This study employs a qualitative approach using the case study method. Data collection techniques were conducted through interviews, observations, and documentation. The results of the study indicate that the school principal plays a strategic role in improving the quality of learning through inspirational leadership, effective resource management, and the implementation of continuous academic supervision. However, there are still several constraints, such as limited facilities and infrastructure, as well as a lack of parental participation. The conclusion of this study is that the role of the school principal is crucial in ensuring the quality of learning; however, support from various stakeholders is necessary to achieve more optimal results.